Psychosocial Correlates, Psychological Distress, and Quality of Life in Patients with Medically Unexplained Symptoms: A Primary Care Study in Karachi, Pakistan. (November 2014) - Husain, Muhammad Ishrat; Chaudhry, Nasim; Morris, Julie; Zafar, Shehla Naeem; Jaffery, Farhat; Rahman, Raza; Duddu, Venu; Husain, Nusrat
Objective: To examine the psychosocial correlates and association of psychological distress and quality of life (QOL) in patients with medically unexplained symptoms (MUS) compared to those with medically explained symptoms (MES) in a primary care setting in Karachi, Pakistan. Methods: A cross-sectional study of 472 patients attending GP clinics between March and August 2009 in Karachi. Participants completed questionnaires to assess demographic details, somatic symptoms, anxiety, depression, and QOL. The patients' GP recorded whether the presenting complaint was medically unexplained or medically explained. Results: MUS subjects in our study were more educated, had better social support and fewer financial problems, were less depressed and had a better QOL than subjects who had medically explained symptoms (non-MUS). Both groups (MUS and non-MUS) were comparable in terms of anxiety and number of somatic symptoms, but non-MUS subjects were more depressed than the MUS group. In a regression analysis, the number of somatic symptoms and lower levels of anxiety predicted poorer QOL in this sample. Whether these symptoms were medically explained (or not) did not seem to contribute significantly to the QOL. Conclusion: Our findings confirm that even in the developing world, patients with MUS are common among primary care attendees. However, patients with MUS in urban Karachi, Pakistan may differ from Western MUS subjects in the role of stress, support, and anxiety in their presentation, and may be reflective of a conceptually different group of difficulties.